PERAN DAN TANTANGAN E-COMMERCE SEBAGAI MEDIA AKSELERASI MANAJEMEN RANTAI NILAI PRODUK PERTANIAN - Eka Nurjati (Forum penelitian Agro Ekonomi, 2021)
E-commerce is growing rapidly along with the increasing use of the internet, particularly in the Covid-19 pandemic. However, the adoption of e-commerce has obstacles, namely the low capability of human resources and infrastructure readiness. This writing aims to identify the roles and challenges of e-commerce agricultural products, review the management aspects of e-commerce agricultural products, and formulate recommendations for e-commerce development in Indonesia. The method is a literature review. E-commerce is a technology that cuts the agricultural value chain. However, it has challenges in implementation, namely no durable, perishable, human resources are not yet compatible, tax regulations, and the quality of the internet. The establishment of e-commerce has a social mission, namely increasing the farmers’ welfare. It aims to overcome the farmer's problems, namely limited access to market and finance. Recommendations for optimizing the value chain by using e-commerce should be carried out through a dimensional approach, namely human resources, natural resources, technology, markets, and finance. The implementation increases the capability of human resources, optimizing the use of natural resources, and developing science and technology.